Pedagogical Mediation and Learning - Delgado Álvarez, Alberto (2014)
The educational act is a complex process. Teaching is an art. Even at present time, most classes in different institutions, schools, high schools or universities, are orthodox lectures that make the students lose their interest for learning. Pedagogical mediation is a valuable instrument that should be applied by most educators so that the educational act does not end up being a monotonous and boring suffering for learners.